Aplikasi Kas Masuk Dan Kas Keluar Pada Almal Laundry Pontianak - Minhad, Yulia; Arizona, Nanda Diaz (Jurnal Gemilang Informatika (GIT), 2023)
Almal Laundry is a washing service business that still uses book records or notes to manage incoming cash, outgoing cash and recapitulation reports. The methodology used in this study uses the waterfall method. The results of the following research are in the form of an application system design that is able to manage incoming and outgoing cash data. This web-based cash-in and cash-out data management application was created using the programming language PHP (Hypertext Preprocessor) as a tool and running the software, Sublime Text 3 as the source code editor, MySQL as database, Php MyAdmin as database editor, and Xampp version 7.3 .6 as the web server. And the output generated in this web-based application includes general ledger reports, cash-in and cash-out reports. With the application of cash in and cash out at the web-based Almal Laundry Pontianak, it is hoped that it can manage cash in and cash out data more effectively and efficiently and the current application system is more conducive